N-Alkyl-1,5-dideoxy-1,5-imino-L-fucitols as fucosidase inhibitors: synthesis, molecular modelling and activity against cancer cell lines - Zhou, Jian; Warta, Rolf; Herold-Mende, Christel (Bioorganic chemistry, 2019)
1,5-Dideoxy-1,5-imino-l-fucitol (1-deoxyfuconojirimycin, DFJ) is an iminosugar that inhibits fucosidases. Herein, N-alkyl DFJs have been synthesised and tested against the α-fucosidases of T. maritima (bacterial origin) and B. taurus (bovine origin). The N-alkyl derivatives were inactive against the bacterial fucosidase, while inhibiting the bovine enzyme. Docking of inhibitors to homology models, generated for the bovine and human fucosidases, was carried out. N-Decyl-DFJ was toxic to cancer cell lines and was more potent than the other N-alkyl DFJs studied.
Available online 04 December 2018
Gesehen am 18.09.2019